2016
DOI: 10.1186/s13018-016-0423-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of anterior cruciate ligament-deficient knees in a Chinese population during stair ascent

Abstract: BackgroundThe purpose of this study was to measure the tibiofemoral kinematics of anterior cruciate ligament (ACL) deficiency in a Chinese population and compare the kinematics with published data about a Caucasian population.MethodsUnilateral knees of 18 Chinese ACL-deficient (ACL-D) subjects were studied while subjects ascended stairs. Kinematic alteration was compared between ACL-D knees and contralateral ACL-intact (ACL-I) knees. The kinematic alteration of ACL deficiency was also compared between the Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The biomechanical effects of ACL were shown in Table 13. In the knee kinematics aspect, Zhao et al [90] reported that the knee ROM was lower for ACL-injured patients in stair climbing. Slater et al [91] pointed out that the peak knee flexion angle was smaller and the peak knee adduction angle was greater for the ACL injury patients in walking.…”
Section: Knee Musculoskeletal Disorders and Its Biomechanicalmentioning
confidence: 99%
“…The biomechanical effects of ACL were shown in Table 13. In the knee kinematics aspect, Zhao et al [90] reported that the knee ROM was lower for ACL-injured patients in stair climbing. Slater et al [91] pointed out that the peak knee flexion angle was smaller and the peak knee adduction angle was greater for the ACL injury patients in walking.…”
Section: Knee Musculoskeletal Disorders and Its Biomechanicalmentioning
confidence: 99%
“…Another limitation of the study is the lack of information about TKA stability. The protocol did not include neither challenging tasks for knee stability, such as stairs climbing, 32,33 nor a measure to detect knee instability, such as anteroposterior displacement of the knee, during gait as it might be now assessed by the KneeKG system. [34][35][36][37] Another weakness is the lack of assessment of the quadriceps muscle strength that plays an important role in the recovery of gait function.…”
Section: Limitationsmentioning
confidence: 99%